Incidence and disease burden of prostate cancer from 1990 to 2017: Results from the Global Burden of Disease Study 2017. Issue 9 (3rd February 2020) - Zhai, Zhen; Zheng, Yi; Li, Na; Deng, Yujiao; Zhou, Linghui; Tian, Tian; Yang, Si; Hao, Qian; Song, Dingli; Wu, Ying; Zhang, Dai; Wang, Ziming; et al.
Abstract : Background: The patterns of the incidence and mortality of prostate cancer (PC) have been changing over the years. In addition, the unclear etiology of PC necessitates further studies into the geographic distribution and age composition of patients with PC. This study was aimed at examining the patterns of the epidemiology of PC to help policymakers to allocate the limited resources of the health care system accordingly. Methods: Annual case data and age‐standardized rates (ASRs) were obtained for the incidence, mortality, and disability‐adjusted life‐years (DALYs) of PC according to age from 1990 to 2017 and for 21 regions, including 195 countries and territories. The estimated annual percentage changes (EAPCs) of ASRs were calculated to evaluate the incidence and mortality trends of PC. Results: Worldwide, the age‐standardized incidence rate (ASIR) of PC increased from 30.5 cases per 100, 000 population in 1990 to 37.9 cases per 100, 000 population in 2017 with an EAPC of 0.59 (95% confidence interval [CI], 0.49‐0.7), whereas the mortality decreased with an EAPC of −0.73 (95% CI, −0.80 to −0.67). The ASIR was positively associated with the sociodemographic index (SDI) in most regions, and the increase in the ASIR was steeper with a higher SDI. The proportion of patients younger than 65 years increased from 23.6% in 1990 to 27.3% in 2017. Conclusions: The incidence of PC has been increasing globally, whereas its mortality and DALYs have been decreasing. These trends are particularly significant in developed regions and vary across geographic regions. Adjustments to the medical strategy by governments and medical institutions are required. Abstract : Prostate cancer's increasing trend for incidence and decreasing trend for mortality are particularly significant in developed regions and vary across geographic regions. In addition, the age composition for prostate cancer has been changing over the years.